Beyond Petroleum: A look at the impact of electric cars in the three main cities of Ecuador - Maks Davis, Michael (Estoa. Journal of the Faculty of Architecture and Urbanism, 2017)
The purpose of this paper is to study the impact of changing private vehicles in Ecuador’s three main cities from combustion engines to their electric counterparts, and to assess whether the newly created electricity demand could be met by renewable energies located within the city boundaries. The work studies Ecuador’s three main cities: Quito, Guayaquil and Cuenca. It was found that in theory and in the extreme case, if there were a sudden change where all the cars and SUVs of Quito were to be replaced by electric vehicles, an electricity demand would be created that could be satisfied through roof installed solar PV within the city boundaries. It would not be feasible however, to do this through wind power. Overall, it was recognised that in reality the changeover to electric vehicles is not likely to be sudden, plus that a transition to electric cars and SUVs only works towards partially solving the problem of fossil fuel demands from the transport sector, but has little impact on the issue of congestion and space requirements. As such, mass transit, multi-modal, electric transport systems have an important role to play in this context for the next stage of research. Keywords: electric cars, private vehicles, public transport, renewable energies, Urban Metabolism.